Preparation and application of hierarchical porous all-silicon zeolite confined copper-bismuth Janus nanoparticle adsorbent

By synthesizing hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbents and utilizing the synergistic effect of copper and bismuth, the problem of poor stability of existing zeolite-based adsorbents under high temperature and high acid conditions was solved, achieving efficient and stable radioactive iodine capture and reducing production costs.

CN117482894BActive Publication Date: 2025-10-14SOUTHWEAT UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311471093.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2025-10-14
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

Existing zeolite-based adsorbents have poor stability under high temperature and high acid conditions, are expensive, and are difficult to effectively capture radioactive iodine, especially 129I. In addition, silver-based zeolites increase production costs and the risk of material oxidation and dissolution.

Method used

A co-reduction-in situ confinement strategy was adopted to synthesize hierarchical pore all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent. Through the synergistic effect of copper and bismuth, thermodynamically stable CuI and BiI3 were formed. The hierarchical pore structure of all-silica zeolite was utilized to improve the stability of the adsorbent and the iodine adsorption capacity.

Benefits of technology

It achieves efficient and stable radioactive iodine capture, avoids the oxidation and loss of metal species, significantly improves the iodine solidification ability of the adsorbent, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117482894B_ABST
    Figure CN117482894B_ABST
Patent Text Reader

Abstract

The application discloses a kind of preparation and application of multi-level hole full-silica zeolite limited copper-bismuth Janus nanoparticle adsorbent, comprising: copper salt and bismuth salt are dissolved in dilute nitric acid solution and then added into deionized water, to obtain bimetallic salt solution;Metal salt solution is added to the raw material for synthesizing full-silica zeolite to pre-crystallize, to obtain gelatinous solution;The obtained gelatinous solution is moved into reaction kettle to carry out hydrothermal crystallization;The obtained sample is filtered, washed, dried, and calcined under inert gas protection, to obtain multi-level hole full-silica zeolite limited copper-bismuth Janus nanoparticle adsorbent.The adsorbent prepared in the application has a multi-level hole structure of microporous-mesoporous, which can avoid oxidation and loss of metal particles during the adsorption process, and the adsorbent is applied to remove radioactive iodine gas, showing high iodine adsorption capacity, and reacting with iodine molecules to form thermodynamically stable CuI and BiI3, further improving the iodine solidification capacity of the adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of nuclear fuel reprocessing, and particularly relates to a preparation method and application of a multi-level hole full-silicon zeolite limited copper-bismuth Janus nanoparticle adsorbent. BACKGROUND

[0002] Nuclear power operation and spent fuel reprocessing will produce radioactive waste gas such as 3 H、 14 C、 129 I、 131 I、 85 Kr、 133 Xe, etc. Among them 129 I is 235 U fission product, because of its long half-life (1.6 x 10 7 years), high content, toxicity, and easy volatilization and strong flow characteristics. UO x When the spent fuel is dissolved in boiling nitric acid solution, most of the CsI is oxidized to volatile radioactive I2 129 I、 131 I), which will cause human metabolic disorders, low intelligence and increase the risk of thyroid cancer and other diseases if released into the environment, and must be purified.

[0003] In order to effectively capture guest iodine molecules, people have made great efforts to enhance the interaction between host adsorbents and radioactive iodine, including metal-based reactions, Lewis acid-base interactions, hydrophobic interactions, electrostatic interactions and van der Waals force interactions. It has important academic value and application prospect to explore and develop adsorbent materials with strong iodine binding capacity, high iodine adsorption and excellent thermal stability. So far, a variety of adsorbent materials have been used to explore the removal of radioactive iodine, among which porous materials such as activated carbon, zeolite, porous organic materials (COFs, POPs, etc.) and metal organic framework materials (MOFs) have shown great advantages in capturing radioactive iodine due to their high specific surface area and porosity, adjustable pore size, rich active sites and functionalization, etc. Multifunctional characteristics, and also are the current research hotspot of adsorbent materials.

[0004] Among various adsorbents, zeolites have considerable potential for iodine capture due to their high stability and ease of mass production. Because most zeolites have low intrinsic iodine adsorption capacity, silver-based zeolites are currently commonly used in post-processing processes to capture iodine. Silver particles are introduced as active adsorption sites through ion exchange or impregnation. Zeolite-loaded silver particles can strongly bind to iodine by converting iodine molecules into silver iodide (AgI), thereby achieving efficient iodine capture. For example, application No. 201480057522.3 discloses a radioactive iodine adsorbent and method for treating radioactive iodine. This radioactive iodine adsorbent is formed by granulating X-type zeolite. By replacing the ion exchange sites of the X-type zeolite with silver, the size of the X-type zeolite's micropores is adapted to the size of hydrogen molecules, allowing it to adsorb radioactive iodine. However, the use of silver significantly increases the production cost of the adsorbent. Furthermore, under extreme conditions such as high temperature and high acidity, the active metal components in the material can oxidize or dissolve, and the reduced material stability makes its practical application still a significant challenge. Therefore, designing and synthesizing new multifunctional materials with high stability is of great significance for the efficient capture of radioactive iodine in post-processing processes. Summary of the Invention

[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0006] In order to achieve these objects and other advantages according to the present invention, a method for preparing a multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent is provided, comprising the following steps:

[0007] Step 1: dissolving copper salt and bismuth salt in a dilute nitric acid solution and then adding deionized water to obtain a bimetallic salt solution;

[0008] Step 2: adding the raw material for synthesizing all-silica zeolite to the bimetallic salt solution in step 1 for pre-crystallization to obtain a gel solution;

[0009] Step 3: transferring the gel solution obtained in step 2 into a reactor for hydrothermal crystallization;

[0010] Step 4: Filter, wash, dry, and calcine the sample obtained in step 3 under the protection of inert gas to obtain a hierarchical pore all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent.

[0011] Preferably, in the step 1, the copper salt is any one of copper nitrate, copper sulfate, copper carbonate, and copper chloride, the bismuth salt is any one of bismuth nitrate and bismuth chloride, the concentration of dilute nitric acid is 1 to 2 mol / L, the dosage is 1 mL, the amount of deionized water is 20 mL, and the molar volume ratio of the copper salt, bismuth salt, dilute nitric acid and deionized water is 0.5 to 2 mol: 0.25 to 1 mol: 1 ml: 20 ml.

[0012] Preferably, in the step 2, the raw materials for synthesizing the all-silica zeolite include a silicon source, a template, a mineralizer, and deionized water. In the steps 1 to 2, the molar volume ratio of the copper salt, bismuth salt and the silicon source, template, mineralizer, and deionized water is 0.005-0.02 mol: 0.0025-0.01 mol: 5-10 mL: 1-5 mL: 10-60 mL: 20 mL.

[0013] Preferably, the silicon source is any one of tetraethyl silicate, silica sol, fumed silica, and white carbon black, the template is any one of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetraethylammonium hydroxide, and hexadecyltrimethylammonium bromide, and the mineralizer is any one of ammonium fluoride, sodium fluoride, and potassium fluoride.

[0014] Preferably, in step 2, the pre-crystallization condition is stirring at 90° C. for 24 to 48 hours.

[0015] Preferably, in step three, the hydrothermal crystallization is carried out at 100-160° C. for 96-120 hours.

[0016] Preferably, in step 4, the drying condition is 60-80° C. for 12-48 hours.

[0017] Preferably, in step 4, the inert gas is 4% H2 / Ar, and the calcination conditions are a heating rate of 5°C / min, a calcination temperature of 550°C, and a holding time of 5h.

[0018] Preferably, in the step 1, before dissolving the copper salt and bismuth salt in the dilute nitric acid solution, the surface of the bismuth salt is first modified to be porous, and the method is as follows: 2 to 4 parts of bismuth salt, 1 to 2 parts of titanium sulfate, and 5 to 10 parts of polyethylene glycol are mixed uniformly by mass, and then 600 to 800 parts of deionized water are added thereto for ultrasonic dispersion at a frequency of 35 to 60 kHz and a dispersion time of 20 to 30 min to obtain a mixed solution, and the mixed solution is heated to 120 to 200 ° C at a heating rate of 1 to 2 ° C / min, and a hydrothermal reaction is carried out in a reactor for a reaction time of 5 to 10 hours. After the reaction, it is cooled to room temperature, filtered, and then washed with deionized water 3 to 5 times. After washing, it is placed in a freeze drying oven and dried at minus 40 ° C for 4 to 8 hours to obtain a surface porous modified bismuth salt.

[0019] A hierarchical pore all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent is used in removing radioactive iodine gas. The prepared hierarchical pore all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent is placed in a radioactive iodine gas environment to achieve the removal of radioactive iodine gas.

[0020] The present invention includes at least the following beneficial effects: The present invention adopts a co-reduction-in-situ confinement strategy to design and synthesize a fully silica zeolite confined copper-bismuth Janus nanoparticle adsorbent containing intracrystalline mesopores. Due to the synergistic effect between the bimetallic Janus structure and the fully silica zeolite, the prepared adsorbent exhibits excellent stability and iodine adsorption capacity. The multi-level pore structure of micropores and mesopores gives the fully silica zeolite a special spatial confinement effect, which can greatly improve the atomic utilization rate and avoid the oxidation and loss of metal species during the reaction. At the same time, the introduction of copper and bismuth can significantly enhance the iodine solidification ability of the adsorbent, and the reaction forms thermodynamically stable CuI and BiI3, thereby realizing efficient solidification treatment of radioactive iodine-containing waste.

[0021] Other advantages, objectives and features of the present invention will be reflected in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 TEM image of the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0023] Figure 2 This is a high-resolution TEM image of the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0024] Figure 3 TEM images of oxygen, silicon, copper, and bismuth in the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0025] Figure 4 TEM image of oxygen in the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0026] Figure 5 TEM image of copper in the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0027] Figure 6 TEM image of bismuth element in the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0028] Figure 7 XRD patterns of the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Examples 1 to 3 of the present invention;

[0029] Figure 8N2 adsorption-desorption isotherms and pore size distribution curves of the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention;

[0030] Figure 9 This is a graph showing the adsorption kinetics of gaseous iodine by the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Examples 1-3 of the present invention;

[0031] Figure 10 XRD pattern of the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 of the present invention after adsorbing iodine;

[0032] Figure 11 This is a diagram showing the adsorption kinetics of gaseous iodine by the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Examples 3 and 4 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains. The terms used in this specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0035] Example 1:

[0036] A method for preparing a multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent comprises the following steps:

[0037] Step 1: Dissolve 43.5 mg of copper nitrate and 43.7 mg of bismuth nitrate in 1 mL of 1 mol / L dilute nitric acid solution and add 20 mL of deionized water to obtain a bimetallic salt solution;

[0038] Step 2: Add 8 mL of tetraethyl silicate, 2.5 mL of tetrapropylammonium hydroxide and 20 mL of deionized water to the above-mentioned bimetallic salt solution, stir at 90°C for 24 hours, then slowly add 40 mL of an aqueous solution containing 2 g of ammonium fluoride, and continue stirring at 90°C for 24 hours for pre-crystallization to obtain a gel solution;

[0039] Step 3: Transfer the gel solution into a reactor and perform hydrothermal crystallization at 120°C for 96 hours;

[0040] Step 4: After crystallization, cool naturally to room temperature, filter the solid product, wash with deionized water, dry at 70°C for 24 hours, and calcine at 550°C for 5 hours under 4% H2 / Ar protection to obtain a hierarchical porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent.

[0041] Example 2:

[0042] A method for preparing a multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent comprises the following steps:

[0043] Step 1: Dissolve 87.0 mg of copper nitrate and 87.3 mg of bismuth nitrate in 1 mL of 1 mol / L dilute nitric acid solution and add 20 mL of deionized water to obtain a bimetallic salt solution;

[0044] Step 2: Add 8 mL of tetraethyl silicate, 2.5 mL of tetrapropylammonium hydroxide and 20 mL of deionized water to the above-mentioned bimetallic salt solution, stir at 90°C for 24 hours, then slowly add 40 mL of an aqueous solution containing 2 g of ammonium fluoride, and continue stirring at 90°C for 24 hours for pre-crystallization to obtain a gel solution;

[0045] Step 3: Transfer the gel solution into a reactor and perform hydrothermal crystallization at 120°C for 96 hours;

[0046] Step 4: After crystallization, cool naturally to room temperature, filter the solid product, wash with deionized water, dry at 70°C for 24 hours, and calcine at 550°C for 5 hours under 4% H2 / Ar protection to obtain a hierarchical porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent.

[0047] Example 3:

[0048] A method for preparing a multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent comprises the following steps:

[0049] Step 1: Dissolve 174.0 mg of copper nitrate and 174.6 mg of bismuth nitrate in 1 mL of 1 mol / L dilute nitric acid solution and add 20 mL of deionized water to obtain a bimetallic salt solution;

[0050] Step 2: Add 8 mL of tetraethyl silicate, 2.5 mL of tetrapropylammonium hydroxide and 20 mL of deionized water to the above-mentioned bimetallic salt solution, stir at 90°C for 24 hours, then slowly add 40 mL of an aqueous solution containing 2 g of ammonium fluoride, and continue stirring at 90°C for 24 hours for pre-crystallization to obtain a gel solution;

[0051] Step 3: Transfer the gel solution into a reactor and perform hydrothermal crystallization at 120°C for 96 hours;

[0052] Step 4: After crystallization, the mixture was naturally cooled to room temperature, the solid product was filtered, washed with deionized water, dried at 70°C for 24 hours, and calcined at 550°C for 5 hours under inert gas protection to obtain a multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent.

[0053] Example 4:

[0054] A method for preparing a hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent comprises the following steps: in step 1, before dissolving a copper salt and a bismuth salt in a dilute nitric acid solution, the bismuth salt is first subjected to surface porous modification, the method comprising: uniformly mixing 174.6 mg of bismuth nitrate, 43.7 mg of titanium sulfate, and 220 mg of polyethylene glycol, adding 30 mL of deionized water, and performing ultrasonic dispersion at a frequency of 40 kHz for 25 minutes to obtain a mixed solution; heating the mixed solution to 180°C at a heating rate of 2°C / min, performing a hydrothermal reaction in a reactor for 8 hours, cooling to room temperature after the reaction, filtering, and then washing with deionized water five times. After washing, the mixture is placed in a freeze drying oven and dried for 6 hours to obtain the bismuth salt with a porous surface modification. The surface porous modified bismuth salt contains titanium dioxide obtained through a hydrothermal reaction, which has a larger specific surface area and can effectively increase adsorption. Polyethylene glycol, as a solvent and dispersant, does not participate in the reaction, but is dispersed on the bismuth salt and titanium dioxide obtained through the hydrothermal reaction. After washing, it can fall off the bismuth salt and titanium dioxide, thereby forming a porous structure.

[0055] Other conditions are consistent with those in Example 3.

[0056] Application Example 1:

[0057] To test the adsorption performance of the prepared adsorbent material for gaseous iodine, the following method was used: 20 mg of the hierarchically porous, fully silica zeolite-confined copper-bismuth Janus nanoparticle adsorbent prepared in Examples 1-4 was placed in a 5 mL small crucible. The small crucible was then placed in a large crucible containing 2 g of iodine. The crucible was then sealed and placed in a 75°C oven. After different reaction times, the iodine capture capacity of the adsorbent was calculated by weighing the change in mass before and after adsorption. This was calculated using the following formula:

[0058] Iodine capture amount = (mass of adsorbent after reaction - mass of adsorbent before reaction) / mass of adsorbent before reaction

[0059] In order to determine whether the increase in the mass of the adsorbent in the experimental results was due to adsorption rather than reaction with air to form oxides, a blank control experiment was conducted, in which the adsorbent prepared in Example 1 was placed in an iodine-free air device with other conditions being the same. The final mass was measured and it was found that the final mass of the adsorbent did not change.

[0060] Figures 1-6 This is a transmission electron microscope (TEM) image of the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2. Figure 1 It can be seen that the carrier is a sheet-like all-silica zeolite. Figure 2 It can be seen that the all-silica zeolite presents a porous structure with intracrystalline mesopores. Figure 3 As shown, the bimetallic particles are distributed inside the all-silicon zeolite, with a particle size of 60 to 100 nm. Figure 4 The transmission electron microscope image of oxygen element shows that it is SiO2 in the all-silicon zeolite. Figure 5 The transmission electron microscope image of copper element shows that it is copper element distributed on the all-silicon zeolite. Figure 6 The transmission electron microscope image of bismuth element shows that it is bismuth element distributed on the all-silicon zeolite. Figure 5 and Figure 6 By comparison, it can be seen that the two metals copper and bismuth in the adsorbent are in a side-by-side, asymmetrically distributed janus structure, which is distributed on the all-silica zeolite.

[0061] The structure of the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Examples 1 to 3 was characterized, and the following was obtained: Figure 7 The XRD pattern shown in Figure 7 It can be seen from the standard XRD patterns of copper and bismuth that there is almost no copper phase in Example 1, but as the amount of copper and bismuth increases, the copper phase and bismuth phase in Examples 2 and 3 gradually increase.

[0062] Figure 8 The N2 adsorption-desorption isotherm and pore size distribution curve of the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared in Example 2 are shown. The data show that the specific surface area of ​​the material is 352.90 m 2 / g, and the average pore diameter is 3.23nm.

[0063] The adsorbents prepared in Examples 1 to 3 were subjected to adsorption of gaseous iodine at 75°C. The results were as follows: Figure 9 As shown, the three examples reached saturated adsorption capacity in about 10 hours, with the maximum adsorption capacity for gaseous iodine being 642 mg / g, 753 mg / g, and 826 mg / g. The results of Examples 1 to 3 show that the iodine adsorption capacity gradually increases with increasing copper and bismuth content.

[0064] Figure 10 The XRD pattern of the adsorption material prepared in Example 2 after adsorption of iodine. Figure 5 It can be seen that the hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent forms CuI and BiI3 phases after adsorbing iodine.

[0065] The adsorbent prepared in Example 4 was adsorbed on gaseous iodine at 75°C and reached saturated adsorption capacity in about 10 hours. The maximum adsorption capacity for gaseous iodine was 871 mg / g. The adsorption amount was compared with that in Example 3. Figure 11 As shown, the results of Example 4 show that before dissolving the copper salt and bismuth salt in the dilute nitric acid solution, the surface of the bismuth salt is firstly modified to be porous, and the introduction of metallic titanium can further enhance the adsorption effect of the adsorbent.

[0066] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A method for preparing a multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent, characterized in that: The following steps are involved: Step 1, by mass, 2 to 4 parts of bismuth salt, 1 to 2 parts of titanium sulfate, and 5 to 10 parts of polyethylene glycol are mixed uniformly, and then 600 to 800 parts of deionized water are added thereto, and ultrasonic dispersion is performed at a frequency of 35 to 60 kHz and a dispersion time of 20 to 30 minutes to obtain a mixed solution, and the mixed solution is heated to 120 to 200° C. at a heating rate of 1 to 2° C. / min, and a hydrothermal reaction is carried out in a reactor for 5 to 10 hours. After the reaction, the mixture is cooled to room temperature, filtered, and then washed with deionized water 3 to 5 times. After washing, the mixture is placed in a freeze drying oven and dried at -40° C. for 4 to 8 hours to obtain a surface porous modified bismuth salt; Dissolving copper salt and surface-porous modified bismuth salt in a dilute nitric acid solution and then adding deionized water to obtain a bimetallic salt solution; Step 2: adding the raw material for synthesizing all-silica zeolite to the bimetallic salt solution in step 1 for pre-crystallization to obtain a gel solution; Step 3: transferring the gel solution obtained in step 2 into a reactor for hydrothermal crystallization; Step 4: The sample obtained in step 3 is filtered, washed, dried, and calcined under 4% H2 / Ar protection to obtain a hierarchical pore all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent.

2. The method for preparing the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent according to claim 1, characterized in that: In the step 2, the pre-crystallization condition is stirring at 90° C. for 24 to 48 hours.

3. The method for preparing the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent according to claim 1, characterized in that: In the step 3, the hydrothermal crystallization condition is 100-160° C. for 96-120 hours.

4. The method for preparing the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent according to claim 1, characterized in that: In the step 4, the drying condition is 60-80° C. for 12-48 hours.

5. The method for preparing the multi-level porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent according to claim 1, characterized in that: In the step 4, the calcination conditions are a heating rate of 5°C / min, a calcination temperature of 550°C, and a holding time of 5h.

6. Use of a hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent prepared by the preparation method according to any one of claims 1 to 5 in removing radioactive iodine gas, characterized in that: The prepared hierarchically porous all-silica zeolite confined copper-bismuth Janus nanoparticle adsorbent is placed in a radioactive iodine gas environment to achieve the removal of radioactive iodine gas.

Citation Information

Patent Citations

  • Radioactive iodine adsorbent and radioactive iodine treatment method

    CN105814643B

  • Preparation method and application of all-silica zeolite confinement copper nanoparticle adsorbent

    CN115178230A

  • Method of removing iodine from gas flows

    RU2414280C1